Lerner, Hagai, And Rothman, Molding The Good Citizen - The Politics Of High School History Texts; Loewen, Lies My Teacher Told Me - Everything Your American History Textbook Got Wrong - Livingston, Jeffery (Teaching History: A Journal of Methods, 1997)
The teaching of American history is a strategic battleground in the culture wars that now rage in the United States. Critics, who often are political conservatives, charge that the history curriculum is deeply flawed. They claim that history has degenerated into a therapeutic multiculturalism more concerned with upholding political correctness than with cultivating national pride and a sense of common heritage. The targets of this attack tend to be liberals and leftists who only now are beginning to respond. They accuse the Right of wanting to return to a nationalistic history that ignores blemishes in the American past and that leaves out women and people of color.